System-Level Performance Analysis of Li-Ion Batteries and DC-DC Converters Under Various Charging Strategies - Tahir, Muhammad Usman; Chakraborty, Sajib; Akboy, Erdem; Sangwongwanich, Ariya; Stroe, Daniel Ioan; Hegazy, Omar; Blaabjerg, Frede (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
Charging strategies play a key role in battery energy storage systems, specifically in applications like electric vehicles. Inefficient charging methods can increase safety risks, performance, and battery life degradation, highlighting the need to develop more advanced charging protocols. Different charging techniques have distinct effects on the LIB and DC-DC converter's electrical and thermal performance. Therefore, this paper investigates different charging techniques in order to determine the LIB and DC-DC converter's electrical and thermal performance parameters. The charging techniques that have been investigated are constant current (CC), multi-stage constant current (MSCC), boost current (BC) charging, and constant power (CP) charging. Results indicate notable variations in charging time, charge input capacity, converter efficiency, and thermal performance across the different strategies. For instance, CC charging exhibits higher efficiency than other charging methods despite differing temperature rise profiles in the DC-DC converter and LIB. Additionally, the CP charging strategy performs well in charged input capacity compared to other methods, with a moderate temperature rise. These results highlight the trade-offs between various performance parameters under different charging strategies. The findings highlight the importance of selecting an appropriate charging strategy based on specific performance targets.
Keywords: Reliability; Fast charging; State of charge; Degradation; DC-DC power converters; Stress; Thermomechanical processes; Lithium; Safety; Protocols; Charging time; electric vehicle; fast charging strategies; Li-ion battery; temperature variation; DC-DC converters; performance analysis; battery management system; controller area network; Engineering